ANTHELMINTIC ACTIVITY OF CHLOROPHYLLIN AGAINST DIFFERENT LARVAL STAGES OF Fasciola gigantica - Divya Jyoti SINGH; Dinesh Kumar SINGH (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Fasciolosis is a food borne zoonosis, caused by the digenetic trematode Fasciola. Freshwater lymnaeid snails are the intermediate host of the trematodes. Chlorophyllin, a semi-synthetic derivative of chlorophyll and its formulations obtained from freeze dried cow urine (FCU) had their toxicity tested against redia and cercaria larvae of F. gigantica. The larvicidal activity of chlorophyllin and its formulations were found to depend on both, time and concentration used against the larvae. Toxicity of chlorophyllin + FCU (1:1 ratio) in sunlight against redia larva (8 h LC50: 0.03 mg/mL) was more pronounced than using just chlorophyllin (8 h LC50: 0.06 mg/mL). Toxicity of chlorophyllin + FCU in sunlight against redia (8 h LC50: 0.03 mg/mL) was higher than against cercaria (8 h LC50: 0.06 mg/mL). The larvicidal activity of chlorophyllin in sunlight (redia/cercaria larvae: 8 h LC50: 0.06 mg/mL) was more pronounced than under laboratory conditions (redia: 8 h LC50: 22.21 mg/mL/, cercaria 8 h LC50: 96.21 mg/mL). Toxicity of FCU against both larvae was lower than that of chlorophyllin and chlorophyllin + FCU. Chlorophyllin and its formulations + FCU were 357.4 to 1603.5 times more effective against redia/cercaria larvae in sunlight than under laboratory conditions. The present study has shown that chlorophyllin formulations may be used as potent larvicides against fasciolosis.